Genetic basis of molecular mechanisms in β-lactam resistant gram-negative bacteria. (September 2021) - Hussain, Haﬁz Iftikhar; Aqib, Amjad Islam; Seleem, Mohamed N.; Shabbir, Muhammad Abubakar; Hao, Haihong; Iqbal, Zahid; Kulyar, Muhammad Fakhar-e-Alam; Zaheer, Tean; Li, Kun
Abstract: Antibiotic-resistant bacteria are considered one of the major global threats to human and animal health. The most harmful among the resistant bacteria are β-lactamase producing Gram-negative species (β-lactamases). β-lactamases constitute a paradigm shift in the evolution of antibiotic resistance. Therefore, it is imperative to present a comprehensive review of the mechanisms responsible for developing antimicrobial resistance. Resistance due to β-lactamases develops through a variety of mechanisms, and the number of resistant genes are involved that can be transferred between bacteria, mostly via plasmids. Over time, these new molecular-based resistance mechanisms have been progressively disclosed. The present review article provides information on the recent findings regarding the molecular mechanisms of resistance to β-lactams in Gram-negative bacteria, including CTX-M-type ESBLs with methylase activity, plasmids harbouring phages with β-lactam resistance genes, the co-presence of β-lactam resistant genes of unique combinations and the presence of β-lactam and non-β-lactam antibiotic-resistant genes in the same bacteria. Keeping in view, the molecular level resistance development, multifactorial and coordinated measures may be taken to counter the challenge of rapidly increasing β-lactam resistance. Graphical abstract: Image 1 Highlights: Antibiotic-resistant bacteria are considered one of the major global threats to human. The most harmful of the resistant bacteria are β-lactamase producing bacteria. Resistance develops through Backspace variety of mechanisms and number of resistant genes. Multifactorial molecular methods should be adopted to counter this challenge.